2023
DOI: 10.1021/acsanm.2c05511
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-heterocyclic carbene)-Protected Water-Soluble Gold Nanoparticles with Tunable Functions for Biosensing Applications

Abstract: Gold nanoparticles (Au NPs) are often susceptible to environmental changes, especially a complexly biological environment, significantly hindering the potential application of biosensors for practical detection. However, the controllable construction of ultrastable water-soluble Au NPs for biosensing applications remains a major challenge today. Here, ultrastable water-soluble Au NPs protected by tris-N-heterocyclic carbene (NHC) ligands (2·Au NPs) have been controllably designed and synthesized. The tris-NHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In sensing analysis, efficient and novel fluorescent materials are also frequently used strategies for the detection of mycotoxins out the other side. Highly efficient luminescent molecular materials have been highly concerned by researchers because they have important application values in many fields, such as luminescent devices, chemical sensors, biological probes, etc. , In 2001, Tang et al first reported the aggregation-induced emission (AIE) effect. AIE molecules have been widely used in the field of chemical biosensors, protein conformation, and chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
“…In sensing analysis, efficient and novel fluorescent materials are also frequently used strategies for the detection of mycotoxins out the other side. Highly efficient luminescent molecular materials have been highly concerned by researchers because they have important application values in many fields, such as luminescent devices, chemical sensors, biological probes, etc. , In 2001, Tang et al first reported the aggregation-induced emission (AIE) effect. AIE molecules have been widely used in the field of chemical biosensors, protein conformation, and chiral recognition.…”
Section: Introductionmentioning
confidence: 99%